2001
DOI: 10.1046/j.1365-2249.2001.01490.x
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in membrane lipid composition, fluidity and respiratory burst in rat peritoneal neutrophils

Abstract: The O2*(-) production has been studied in rat peritoneal neutrophils of different age (3, 12 and 24 months), in order to analyse whether the neutrophil respiratory burst is modified with increasing age. To stimulate NADPH oxidase, the enzyme responsible for the respiratory burst, two stimuli that act in different way have been used: phorbol myristate acetate (PMA) and N-formyl-methionyl-leucyl-phenylalanine (N-FMLP). Production of O2*(-) decreased with age in neutrophils stimulated with N-FMLP (about 40%), but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 57 publications
2
36
0
Order By: Relevance
“…These data are in accordance with those obtained in cultured cells and tissues (1,5,16,29). The increase of membrane fluidity can also be explained by a change in fatty acid lipid composition that causes an increase in free volume between the lipid chains, due to the presence of double bounds in fatty acids (18:2 and 20:4), leading to a bend in the lipid chain itself.…”
Section: Discussionsupporting
confidence: 90%
“…These data are in accordance with those obtained in cultured cells and tissues (1,5,16,29). The increase of membrane fluidity can also be explained by a change in fatty acid lipid composition that causes an increase in free volume between the lipid chains, due to the presence of double bounds in fatty acids (18:2 and 20:4), leading to a bend in the lipid chain itself.…”
Section: Discussionsupporting
confidence: 90%
“…8). Similar changes were seen in hepatocytes from old rats (46), although other studies using various types of tissues have shown enzyme activities to increase (32), decrease (2), and stay the same (6). Glutathione peroxidase has been shown to be essential for the survival of HUVECs after treatment with peroxides (22).…”
Section: Discussionsupporting
confidence: 69%
“…We observed a very small percentage of large cells in our young cultures (Ͻ20 CPD), and these cells tended to stain positive for senescence-associated ␤-galactosidase and were often multinucleated (data not shown). Similarly, multinucleated cells (2)(3)(4)(5)(6)(7)(8)(9)(10) were observed in cultures established from vessels (50). As our cultures increased in CPD, all the cells were seen to increase in size.…”
Section: Discussionmentioning
confidence: 89%
“…Decline in priming and activation of neutrophils in response to LPS, granulocyte CSF (G-CSF), FMLP, and ligation of triggering receptor expressed on myeloid cell 1 has also been reported in elderly humans (101,112,158). Recent studies have implicated defective recruitment of signaling intermediaries into lipid rafts as a potential unifying defect in the signals generated at the membrane (9,343). Future studies will likely establish whether these defects are attributable to altered membrane fluidity, cytoskeletal changes, or altered protein domains.…”
Section: Immune Senescence and Interventionsmentioning
confidence: 99%